25 Years of the GERD-HRQL symptom severity instrument: an assessment of published applications - Velanovich, Vic (Surgical endoscopy, 2023)
Background The GERD-HRQL symptom severity instrument was developed and published 25 years ago. This seems like an apropos time to review how the instrument has been used in the “real-world.” Methods Google Scholar, PubMed, and Web of Science websites search was done using the keywords “GERD-HRQL” or its author, “Velanovich.” Once articles were identified, the following information was obtained from each article: first author name, country of origin, journal published, year of publications, type of study design, subject of study, category of study, disease type studied, purpose of the study, how the GERD-HRQL scores were reported, how the GERD-HRQL scores were statistically reported, and results of the study. The total and change of scores were analyzed for descriptive statistics based on disease process studied and intervention studied. Results A total of 767 articles by 562 different first authors were identified in 193 different journals from 53 different countries of study origin. After a period of steady usages, the number of publication employing the GERD-HRQL has rapidly increase over the last 5 years. There have been 8 validated translations into other languages, although there appears to be numerous, non-validated ad hoc translations. Most commonly used or studied: observational cohort study design, surgical treatment study category, GERD disease process, treatment effect study purpose, total GERD-HRQL scores reported as means or medians. However, there were a wide variety of other study designs, study categories, disease processes, and study purposes. In general, GERD and laryngopharyngeal reflux had the high pre-treatment scores (i.e., more severe symptoms), and surgical and endoscopic interventions the lowest post-treatment score (i.e., least severe symptoms) with the largest change in score (i.e., treatment impact. Conclusions The GERD-HRQL has proven to be a reliable, responsive and versatile symptom severity instrument for studies involving GERD as a subject.